Revisiting Women's Piety Movements in the Indonesian Context - Jati, Wasisto Raharjo; Syamsurijal, Syamsurijal; Halimatusa'diah, Halimatusa'diah; Yilmaz, Ihsan; Rahmiati, Dini (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
The current Islamic studies literature focusing on women’s expression in Indonesia remains understudied. It still presents a scholarly challenge for current Islamic studies to address the issue of ideal expressed space for women. This mainly includes women’s positions and roles in society and their concerns about public issues. Addressing this puzzle, this paper aims to analyse how Islam affirmatively can address women’s expression as individuals and members of social groups. This paper employs critical discourse analysis by cultivating theoretical frameworks such as the debate between feminism and Islamic understandings of women. The findings of this study show that the need for inclusive public space for women to express their concerns while keeping their Islamic faith is imminent. This paper also further investigates how three women movements build up their expressed spaces and their impact on society.